Nano-ceramic reinforced metal-based spherical metal powder, composite material and preparation method thereof

Through ultrasonic resonance mixing and high-temperature molten salt treatment, the problems of uniform dispersion and anti-oxidation agglomeration of nanoceramic particles in the metal matrix are solved, significantly improving the performance of metal-based composite materials and achieving high-performance metal material preparation.

CN119114948APending Publication Date: 2024-12-13MCC KUNYUAN (CHONGQING) METAL MATERIALS RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411262807.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art is difficult to achieve uniform dispersion of nanoceramic particles in metal substrates under high temperature conditions and prevent oxidative agglomeration, resulting in limited improvement in the performance of metal materials.

Method used

Nanoceramic particles are used for ultrasonic resonance mixing with micron-scale metal powder, and mechanically stirring in high-temperature molten salt. The nanoceramic particles are diffused into the metal particles by heating, followed by desalting and hot pressing sintering to form nanoceramic reinforced metal. Base spherical metal powder.

Benefits of technology

The high content uniform dispersion of nanoceramic particles is achieved, which significantly improves the mechanical strength and high temperature resistance of the material, avoids oxidative agglomeration, and improves the overall performance of metal-based composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114948A_ABST
    Figure CN119114948A_ABST
Patent Text Reader

Abstract

The invention relates to nano-ceramic reinforced metal-based spherical metal powder, a composite material and a preparation method of the nano-ceramic reinforced metal-based spherical metal powder, and belongs to the field of metal-based composite materials. The preparation method of the spherical metal powder comprises the following steps: mixing nano ceramic particles and micron-sized metal powder in proportion; adding the metal-ceramic composite mixed powder into the high-temperature molten salt, and mechanically stirring; the temperature of the fused salt is higher than the fused salt melting point; continuously heating the molten salt-ceramic-metal mixture until the temperature of the molten salt-ceramic-metal mixture is higher than a metal melting point, so that the nano ceramic particles are diffused into the micron metal particles; the fused salt-ceramic-metal mixture is subjected to air cooling until the temperature is lower than T1; and the molten salt-ceramic-metal blocky solid is smashed, desalted and dried, and spherical metal powder is obtained. And on the basis, the metal powder is subjected to hot pressed sintering, and the nano ceramic reinforced metal matrix composite is obtained. According to the method, high-content nano ceramic particles can be uniformly dispersed in a metal matrix, so that the performance of the composite material is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal-based composite materials, and relates to a nano-ceramic reinforced metal-based spherical metal powder, a composite material and a preparation method thereof. Background Art

[0002] The mechanical and electrical properties of traditional metal materials are generally limited under high temperature conditions, making it difficult to meet the growing demand for high-performance materials in modern industry. High temperature environments pose higher challenges to the performance of metal materials. The performance of many traditional metal materials decreases significantly at high temperatures, which greatly limits their widespread use in high-end applications. In order to overcome this problem, researchers began to explore the introduction of nano-ceramic particles as hard phase materials into the metal matrix, in order to significantly improve the comprehensive performance of metal-based materials, including mechanical strength, wear resistance, and high temperature resistance.

[0003] However, although the introduction of nano-ceramic particles has brought the possibility of improving performance, their high surface energy and easy agglomeration characteristics have also brought great difficulties to the preparation of materials. How to achieve uniform dispersion of high-content nano-ceramic particles in the metal matrix while avoiding oxidation and agglomeration at high temperatures has always been a technical challenge faced by this field.

[0004] Existing preparation methods, such as traditional high-temperature smelting ultrasonic dispersion and powder metallurgy, have shown certain limitations when trying to solve this problem. In the high-temperature smelting ultrasonic dispersion method, nano-ceramic particles are added after the metal is melted, but due to the violent movement of the high-temperature liquid, the nano-ceramic particles are prone to oxidation and agglomeration. Although ultrasonic technology can alleviate the agglomeration problem to a certain extent, long-term ultrasonic treatment may induce other adverse reactions of nano-ceramic particles at high temperatures, thereby affecting the performance of the composite material. Powder metallurgy usually uses mechanical ball milling to mix metal powder and nano-ceramic particles. However, this method may not only cause deformation of the metal powder and affect the size distribution and shape regularity of the powder, but ball milling dispersion is also not conducive to the composite of high-content nano-ceramic particles, and aggravates the agglomeration tendency of nano-ceramic particles (such as Figure 1 ), which in turn affects the uniformity and overall performance of the material. Not only that, the heat and mechanical stress generated during the mechanical ball milling process may also damage the nano-ceramic particles, further affecting the performance of the final material.

[0005] In summary, existing preparation methods still have limitations in solving the dispersion of nano-ceramic particles and preventing oxidation agglomeration, and the performance improvement of metal materials under high temperature conditions still faces many challenges. Therefore, the development of new preparation technologies to achieve uniform dispersion of high-content nano-ceramic particles in the metal matrix and prevent oxidation agglomeration at high temperatures is of great significance for the preparation of high-performance metal materials. This will provide more high-performance and high-reliability metal material options for modern industry and promote the further development of high-end application fields. Summary of the invention

[0006] In view of this, the object of the present invention is to provide a nano-ceramic reinforced metal-based spherical metal powder, a composite material and a preparation method thereof, so as to achieve uniform dispersion of high-content nano-ceramic particles in the metal matrix, thereby significantly improving the performance of the composite material.

[0007] To achieve the above object, the present invention provides a method for preparing nano-ceramic reinforced metal-based spherical metal powder, comprising the following steps:

[0008] S1: mixing nano-ceramic particles and micron-sized metal powder in proportion by ultrasonic resonance to obtain metal-ceramic composite mixed powder;

[0009] S2: adding the metal-ceramic composite powder mixture into high-temperature molten salt and mechanically stirring it to obtain a molten salt-ceramic-metal mixture; wherein the temperature of the molten salt is between T1 and T2, T1 is the melting point of the molten salt, and T2 is the melting point of the metal powder;

[0010] S3: Continuously heating the molten salt-ceramic-metal mixture until its temperature is higher than T2 and maintaining it for 5 to 30 minutes to allow the nano-ceramic particles to diffuse into the micron-metal particles;

[0011] S4: cooling the molten salt-ceramic-metal mixture by air until its temperature is lower than T1, thereby obtaining a molten salt-ceramic-metal block solid;

[0012] S5: crushing the molten salt-ceramic-metal block solid, desalting the crushed particles with deionized water and drying them to obtain nano-ceramic reinforced metal-based spherical metal powder.

[0013] Optionally, the nano ceramic particles are Al 2 O 3 , Y 2 O 3 、ZrO 2 、Si 3 N 4 , BN, AlN, WC, SiC, TiC, ZrC, TiB 2 , ZrB 2 ,CrB 2 One of them.

[0014] Optionally, the metal powder is a metal or a metal alloy.

[0015] Optionally, the volume purity of the nano-ceramic particles is 95-100%, and the particle size is less than 200 nm.

[0016] Optionally, the volume purity of the metal powder is 95-100% and the particle size is less than 10 μm.

[0017] Optionally, the molten salt is at least one of halides, nitrates, sulfates and carbonates of alkali metals and alkaline earth metals.

[0018] Optionally, in step S1, the volume ratio of nano-ceramic particles to micron-sized metal powder is 2:3.

[0019] Optionally, in step S1, the mass ratio of nano-ceramic particles to micron-sized metal powder is 1:1.

[0020] Optionally, in step S2, the rotation speed of the mechanical stirring is not less than 100 rpm, and the stirring time is not less than 20 min.

[0021] Optionally, metal-ceramic composite micropowder is evenly distributed in the molten salt-ceramic-metal block solid, and the metal-ceramic composite micropowder is manifested as metal microspheres evenly inlaid with nano-ceramic particles;

[0022] Optionally, in step S5, the molten salt-ceramic-metal block solid is ground and crushed to a particle size less than millimeter level.

[0023] Optionally, in step S5, the desalted particles are placed in a vacuum drying oven and dried at 200° C. until no liquid remains.

[0024] The present invention also provides a nano-ceramic reinforced metal-based spherical metal powder prepared according to the method.

[0025] The present invention also provides a method for preparing a nano-ceramic reinforced metal matrix composite material, comprising the following steps:

[0026] Using the aforementioned preparation method to obtain nano-ceramic reinforced metal-based spherical metal powder;

[0027] Under the protection of inert gas, nano-ceramic reinforced metal-based spherical metal powder is hot-pressed and sintered at high temperature and high pressure, and a block-shaped nano-ceramic reinforced metal-based composite material is prepared through a deformation heat treatment process.

[0028] Optionally, the temperature of hot pressing sintering is 1200-1800° C., the pressure of hot pressing sintering is 7-8 MPa, and the time of hot pressing sintering is not less than 30 min.

[0029] Optionally, the inert gas is at least one of helium, neon, argon, krypton, xenon and radon.

[0030] The present invention also provides a nano-ceramic reinforced metal-based composite material prepared according to the method.

[0031] The present invention also provides an alloy product, which is mainly made of the above-mentioned nano-ceramic reinforced metal-based composite material.

[0032] The beneficial effects of the present invention are:

[0033] First, compared with the traditional high-temperature smelting ultrasonic dispersion method and powder metallurgy method, the present invention adopts the method of heating the nanoparticles and molten salt at the same time. The molten salt treatment temperature is lower than the traditional method, which effectively prevents the oxidation of the nanoparticles in a high temperature environment. It also helps to maintain the uniform dispersion of the nanoparticles after acoustic resonance treatment, greatly reducing the possibility of particle agglomeration.

[0034] Secondly, the present invention uses ultrasonic resonance technology to mix powders, which has less effect on the physical and chemical properties of the powders than traditional mechanical ball milling. Ultrasonic resonance not only does not change the original shape of the powder, but also maintains its spherical state, which is crucial for improving the density of subsequent processing. More importantly, ultrasonic resonance technology achieves effective dispersion of high-content nano-ceramic particles, ensuring that the prepared metal-based composite material has a high content and uniform distribution of nano-ceramic particles, thereby significantly improving the overall performance of the material.

[0035] In summary, the present invention not only optimizes the dispersibility and anti-oxidation properties of nano-ceramic particles, but also improves the morphology and dispersibility of powders, providing an innovative and effective way to prepare high-performance metal-based nanocomposites.

[0036] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:

[0038] Figure 1 This is a SEM image of a metal-ceramic composite mixed powder obtained by mechanically ball-milling a metal powder and nano-ceramic particles in the prior art;

[0039] Figure 2A flow chart of a method for preparing a nano-ceramic reinforced metal-based spherical metal powder provided by the present invention;

[0040] Figure 3 This is a SEM image of the metal-ceramic composite powder mixture after ultrasonic resonance mixing in Example 1 of the present invention;

[0041] Figure 4 This is a SEM image of the metal-ceramic composite powder mixture after ultrasonic resonance mixing in Example 2 of the present invention. DETAILED DESCRIPTION

[0042] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.

[0043] Among them, the drawings are only used for illustrative explanations, and they only represent schematic diagrams rather than actual pictures, and should not be understood as limitations on the present invention. In order to better illustrate the embodiments of the present invention, some parts of the drawings may be omitted, enlarged or reduced, and do not represent the size of actual products. For those skilled in the art, it is understandable that some well-known structures and their descriptions in the drawings may be omitted.

[0044] The same or similar numbers in the drawings of the embodiments of the present invention correspond to the same or similar parts; in the description of the present invention, it should be understood that if the terms "upper", "lower", "left", "right", "front", "rear", etc. indicate the orientation or position relationship, they are based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation. Therefore, the terms describing the position relationship in the drawings are only used for illustrative purposes and cannot be understood as limiting the present invention. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.

[0045] The embodiment of the present invention provides a method for preparing a nano-ceramic reinforced metal-based spherical metal powder, such as Figure 2 As shown, the following steps are included:

[0046] S1: mixing nano-ceramic particles and micron-sized metal powder in proportion by ultrasonic resonance to obtain metal-ceramic composite mixed powder;

[0047] S2: adding the metal-ceramic composite powder mixture into high-temperature molten salt and mechanically stirring it to obtain a molten salt-ceramic-metal mixture; wherein the temperature of the molten salt is between T1 and T2, T1 is the melting point of the molten salt, and T2 is the melting point of the metal powder;

[0048] S3: Continuously heating the molten salt-ceramic-metal mixture until its temperature is higher than T2 and maintaining it for 5 to 30 minutes to allow the nano-ceramic particles to diffuse into the micron-metal particles;

[0049] S4: cooling the molten salt-ceramic-metal mixture by air until its temperature is lower than T1, thereby obtaining a molten salt-ceramic-metal block solid;

[0050] S5: crushing the molten salt-ceramic-metal block solid, desalting the crushed particles with deionized water and drying them to obtain nano-ceramic reinforced metal-based spherical metal powder.

[0051] Specifically, in an embodiment of the present invention, the nano ceramic particles are Al 2 O 3 , Y 2 O 3 、ZrO 2 、Si 3 N 4 , BN, AlN, WC, SiC, TiC, ZrC, TiB 2 , ZrB 2 ,CrB 2 One of them.

[0052] Specifically, in the embodiments of the present invention, the metal powder may be any metal and its alloys known to those skilled in the art, such as aluminum, copper, nickel and their alloys.

[0053] Specifically, in the embodiment of the present invention, the volume purity of the nano-ceramic particles is 95-100%, and the particle size is less than 200 nm.

[0054] Specifically, in an embodiment of the present invention, the volume purity of the metal powder is 95-100%, and the particle size is less than 10 μm.

[0055] Specifically, in an embodiment of the present invention, the molten salt is at least one of halides, nitrates, sulfates and carbonates of alkali metals and alkaline earth metals.

[0056] Specifically, in an embodiment of the present invention, the heating time of the molten salt-ceramic-metal mixture in step 3 depends on the type of the selected metal and metal alloy. Exemplarily, the heating time of the molten salt-ceramic-metal mixture is 8 to 30 minutes.

[0057] Specifically, in an embodiment of the present invention, in step S1, the volume ratio of nano-ceramic particles to micron-sized metal powder is 2:3. Within this ratio range, the obtained ceramic-metal spherical metal powder has higher hardness and anti-softening temperature.

[0058] Specifically, in an embodiment of the present invention, in step S1, the mass ratio of nano-ceramic particles to micron-sized metal powder is 1:1. Within this ratio range, the obtained ceramic-metal spherical metal powder has higher hardness and anti-softening temperature.

[0059] Specifically, in an embodiment of the present invention, in step S2, the rotation speed of the mechanical stirring is not less than 100 rpm, and the stirring time is not less than 20 min.

[0060] Specifically, in the embodiment of the present invention, metal-ceramic composite micropowder is evenly distributed in the molten salt-ceramic-metal block solid, and the metal-ceramic composite micropowder is manifested as metal microspheres evenly inlaid with nano-ceramic particles;

[0061] Specifically, in an embodiment of the present invention, in step S5, the molten salt-ceramic-metal block solid is ground and crushed to a particle size less than millimeter level.

[0062] Specifically, in an embodiment of the present invention, in an embodiment of the present invention, in step S5, the desalted particles are placed in a vacuum drying oven and dried at 200° C. until no liquid remains.

[0063] An embodiment of the present invention also provides a nano-ceramic reinforced metal-based spherical metal powder prepared according to the above method.

[0064] The embodiment of the present invention also provides a method for preparing a nano-ceramic reinforced metal matrix composite material, comprising the following steps:

[0065] S1: using the aforementioned preparation method to obtain nano-ceramic reinforced metal-based spherical metal powder;

[0066] S2: Under the protection of inert gas, the nano-ceramic reinforced metal-based spherical metal powder is hot-pressed and sintered at high temperature and high pressure, and a block-shaped nano-ceramic reinforced metal-based composite material is prepared through a deformation heat treatment process.

[0067] Specifically, in an embodiment of the present invention, the temperature, pressure and time of hot pressing sintering are determined according to the type of metal and metal alloy selected. Exemplarily, the temperature of hot pressing sintering is 1200-1800°C, the pressure of hot pressing sintering is 7-8MPa, and the time of hot pressing sintering is not less than 30min.

[0068] Specifically, in an embodiment of the present invention, the inert gas is at least one of helium, neon, argon, krypton, xenon and radon.

[0069] An embodiment of the present invention also provides a nano-ceramic reinforced metal matrix composite material prepared according to the above method.

[0070] An embodiment of the present invention further provides an alloy product, which is mainly made of the above-mentioned nano-ceramic reinforced metal-based composite material.

[0071] Example 1

[0072] A method for preparing a nano-ceramic reinforced metal matrix composite material, using pure Cu powder and WC nanoparticles as raw materials, specifically comprising the following steps:

[0073] (1) Pure Cu powder and WC nanoparticles were mixed by ultrasonic resonance at a volume ratio of 3:2 to obtain Cu-WC composite mixed powder;

[0074] (2) After heating 100 g of NaCl to 850 °C to melt, 100 g of Cu-WC composite powder was added to the molten salt and mechanically stirred for 30 min to obtain a NaCl-WC-Cu mixture;

[0075] (3) Continuously heating the NaCl-WC-Cu mixture to 1200°C and maintaining it for 30 min;

[0076] (4) cooling the NaCl-WC-Cu mixture to below 850° C. by air cooling to obtain a NaCl-WC-Cu block solid;

[0077] (5) crushing the NaCl-WC-Cu block solid, and soaking the crushed particles in deionized water for 3 rounds to fully dissolve the NaCl, and then placing the crushed particles in a vacuum drying oven and drying at 200° C. until no liquid remains, thereby obtaining nano-tungsten carbide particle-reinforced copper-based spherical metal powder;

[0078] (6) Under the protection of argon, the copper-based spherical metal powder reinforced with nano-tungsten carbide particles was melted at a temperature of 1500°C and a pressure of 7.5 MPa for 30 min, and a bulk Cu / 40 vol.% WC composite material sample was prepared by a deformation heat treatment process.

[0079] The volume purity of the pure Cu powder in this embodiment is 99%, and the particle size is <10 μm; the volume purity of the WC nano-ceramic particles is 99.9%, and the average particle size is 150-200 nm.

[0080] In step 1 of this embodiment, the ultrasonic frequency is 1 kHz and the mixing time is 10 min.

[0081] The scanning electron microscope observation results of the Cu-WC composite powder obtained in step 1 of the present embodiment are as follows: Figure 3As shown, it can be seen that the WC particles are evenly distributed on the Cu surface without obvious agglomeration.

[0082] In step 2 of this embodiment, the volume purity of the NaCl particles is 99.5%, and the rotation speed of the mechanical stirring is not less than 100 rpm.

[0083] Example 2

[0084] A method for preparing a nano-ceramic reinforced metal matrix composite material, using pure CuTi powder and SiC nanoparticles as raw materials, specifically comprises the following steps:

[0085] (1) CuTi powder and SiC nanoparticles are mixed by ultrasonic resonance at a mass ratio of 1:1 to obtain a CuTi-SiC composite mixed powder;

[0086] (2) 300g KNO 3 After heating to 500℃ and melting, 200g of CuTi-SiC composite powder was added to the molten salt and mechanically stirred for 20min to obtain KNO 3 -CuTi-SiC mixture;

[0087] (3) Continuous heating of KNO 3 -CuTi-SiC mixture to 1100°C and maintain for 8 minutes;

[0088] (4) KNO 3 -CuTi-SiC mixture is cooled to below 500℃ by air cooling to obtain KNO 3 -CuTi-SiC bulk solid;

[0089] (5) Crushing KNO 3 -CuTi-SiC block solid, and the crushed particles were soaked in deionized water for 3 rounds to fully dissolve KNO 3 The crushed particles are then placed in a vacuum drying oven and dried at 200°C until no liquid remains, thereby obtaining nano-silicon carbide particle-reinforced copper-based spherical metal powders;

[0090] (6) Under the protection of argon, the copper-based spherical metal powder reinforced with nano-silicon carbide particles was melted at a temperature of 1400°C and a pressure of 7 MPa for 30 min, and a bulk CuTi / 50wt.% SiC composite material sample was prepared by a deformation heat treatment process.

[0091] The volume purity of the pure CuTi powder in this embodiment is 99%, and the particle size is <10 μm; the volume purity of the SiC nano-ceramic particles is 99.9%, and the average particle size is 20-50 nm.

[0092] In step 1 of this embodiment, the ultrasonic frequency is 5 kHz and the mixing time is 8 min.

[0093] The scanning electron microscope observation results of the CuTi-SiC composite mixed powder obtained in step 1 of this embodiment are as follows: Figure 4 As shown, it can be seen that SiC particles are evenly distributed on the CuTi surface without obvious agglomeration.

[0094] In step 2 of this embodiment, KNO 3 The volume purity of the particles is 99.5%, and the rotation speed of the mechanical stirring is not less than 100 rpm.

[0095] Pure copper powder was used as a comparative sample, and the Cu / 40 vol.% WC composite material prepared in Example 1 and the CuTi / 50 wt.% SiC composite material prepared in Example 2 were used as experimental samples. Their average hardness and softening resistance temperature were tested respectively. The results are shown in Table 1.

[0096] Table 1

[0097] Material Type Average hardness / HV Anti-softening temperature / ℃ Pure Copper ~56.5 ~250 Example 1 ~123.2 ~725 Example 2 ~108.2 ~800

[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing nano-ceramic reinforced metal-based spherical metal powder, characterized in that: The following steps are involved: S1: mixing nano-ceramic particles and micron-sized metal powder in proportion by ultrasonic resonance to obtain metal-ceramic composite mixed powder; S2: adding the metal-ceramic composite powder mixture into high-temperature molten salt and mechanically stirring to obtain a molten salt-ceramic-metal mixture; wherein the temperature of the molten salt is between T1 and T2, T1 is the melting point of the molten salt, and T2 is the melting point of the metal powder; S3: continuously heating the molten salt-ceramic-metal mixture until its temperature is higher than T2, and maintaining it for 5 to 30 minutes, so that the nano-ceramic particles diffuse into the micron metal particles; S4: air-cooling the molten salt-ceramic-metal mixture until its temperature is lower than T1 to obtain a molten salt-ceramic-metal block solid; S5: crushing the molten salt-ceramic-metal block solid, desalting the crushed particles with deionized water and drying them to obtain nano-ceramic reinforced metal-based spherical metal powder.

2. The preparation method according to claim 1, characterized in that: The nano ceramic particles are one of Al2O3, Y2O3, ZrO2, Si3N4, BN, AlN, WC, SiC, TiC, ZrC, TiB2, ZrB2, and CrB2.

3. The preparation method according to claim 1, characterized in that: The metal powder is metal or metal alloy.

4. The preparation method according to claim 1, characterized in that: The volume purity of the nano ceramic particles is 95-100%, and the particle size is less than 200nm.

5. The preparation method according to claim 1, characterized in that: The volume purity of the metal powder is 95-100%, and the particle size is less than 10 μm.

6. The preparation method according to claim 1, characterized in that: The molten salt is at least one of halides, nitrates, sulfates and carbonates of alkali metals and alkaline earth metals.

7. The preparation method according to claim 1, characterized in that: In the step S1, the volume ratio of nano-ceramic particles to micron-sized metal powder is 2:

3.

8. The preparation method according to claim 1, characterized in that: In the step S1, the mass ratio of the nano-ceramic particles to the micron-sized metal powder is 1:

1.

9. The preparation method according to claim 1, characterized in that: In step S2, the rotation speed of the mechanical stirring is not less than 100 rpm, and the stirring time is not less than 20 min.

10. The preparation method according to claim 1, characterized in that: The metal-ceramic composite micropowder is evenly distributed in the molten salt-ceramic-metal block solid, and the metal-ceramic composite micropowder is in the form of metal microspheres evenly inlaid with the nano-ceramic particles.

11. The preparation method according to claim 1, characterized in that: In the step S5, the molten salt-ceramic-metal block solid is ground and crushed to a particle size less than millimeter level.

12. The preparation method according to claim 1, characterized in that: In step S5, the desalted particles are placed in a vacuum drying oven and dried at 200° C. until no liquid remains.

13. Nano-ceramic reinforced metal-based spherical metal powder prepared according to the method according to any one of claims 1 to 12.

14. A method for preparing a nano-ceramic reinforced metal matrix composite material, characterized in that: Using the preparation method as described in any one of claims 1 to 12 to obtain nano-ceramic reinforced metal-based spherical metal powder; Under the protection of inert gas, the nano-ceramic reinforced metal-based spherical metal powder is hot-pressed and sintered at high temperature and high pressure, and a block-shaped nano-ceramic reinforced metal-based composite material is prepared through a deformation heat treatment process.

15. The preparation method according to claim 14, characterized in that: The temperature of the hot pressing sintering is 1200-1800° C., the pressure of the hot pressing sintering is 7-8 MPa, and the time of the hot pressing sintering is not less than 30 minutes.

16. The nano-ceramic reinforced metal matrix composite material prepared by the method according to claim 14.

17. An alloy product, characterized in that: The alloy product is mainly made of the nano-ceramic reinforced metal-based composite material described in claim 16.